Genetic variants associated with T cell–mediated cutaneous adverse drug reactions: A PRISMA‐compliant systematic review—An EAACI position paper. Issue 5 (18th May 2020) - Oussalah, Abderrahim; Yip, Vincent; Mayorga, Cristobalina; Blanca, Miguel; Barbaud, Annick; Nakonechna, Alla; Cernadas, Josefina; Gotua, Maia; Brockow, Knut; Caubet, Jean‐Christoph; Bircher, Andreas; Atanaskovic‐Markovic, Marina; et al.
Abstract: Drug hypersensitivity reactions (DHRs) are associated with high global morbidity and mortality. Cutaneous T cell–mediated reactions classically occur more than 6 hours after drug administration and include life‐threatening conditions such as toxic epidermal necrolysis, Stevens‐Johnson syndrome, and hypersensitivity syndrome. Over the last 20 years, significant advances have been made in our understanding of the pathogenesis of DHRs with the identification of human leukocyte antigens as predisposing factors. This has led to the development of pharmacogenetic screening tests, such as HLA‐B*57:01 in abacavir therapy, which has successfully reduced the incidence of abacavir hypersensitivity reactions. We have completed a PRISMA‐compliant systematic review to identify genetic associations that have been reported in DHRs. In total, 105 studies (5554 cases and 123 548 controls) have been included in the review reporting genetic associations with carbamazepine (n = 31), other aromatic antiepileptic drugs (n = 24), abacavir (n = 11), nevirapine (n = 14), trimethoprim‐sulfamethoxazole (n = 11), dapsone (n = 4), allopurinol (n = 10), and other drugs (n = 5). The most commonly reported genetic variants associated with DHRs are located in human leukocyte antigen genes and genes involved in drug metabolism pathways. Increasing our understanding of genetic variants that contribute to DHRs will allow us to improve diagnosis, develop new treatments, and predict and prevent DHRs in the future.